Effect of Retort Sterilization Temperature and Time on the Quality of Vacuum Packed Soft-Boned Milkfish - Lusi Maswahyu Andriyani; Sunyoto; Siti Harnina Bintari; Pramesti Dewi; Dewi Mustikaningtyas (Universitas Negeri Semarang, 2026)
Soft-boned milkfish is a popular processed product of the milkfish (Chanos chanos), but it has a limited shelf life. Retort sterilization technology with vacuum retort pouch packaging can extend shelf life, but it is necessary to study the right combination of temperature and time to maintain product quality. This study aims to analyze the effect of a combination of temperature (110 °C, 121 °C, and 130 °C) and sterilization time (10, 20, and 30 min) on Total Plate Count (TPC), total protein content, and hedonic quality of the product. The parameters analyzed in this study were TPC with two replications (duplicates), total protein content measured by the Biuret method, and hedonic quality assessed through the hedonic test. The results showed that all treatments produced TPC below the SNI 7388:2009 limit of 5 × 105 CFU/g. The 121 ℃ treatment for 30 min maintained a total protein content of 26.17% and TPC value of 1.00 × 10² CFU/g, while the 130 ℃ treatment for 10 min produced a total protein content of 20.85% and TPC value of 1.00 × 10⁰ CFU/g, and produced the most favorable hedonic quality. Therefore, 130 °C for 10 min is recommended as the optimal sterilization temperature and time, because it is able to produce products that are microbiologically safe and preferred by panelists. Moisture content plays a role in influencing TPC value, total protein content, and hedonic quality. It is recommended to research the effect of temperature and sterilization time of soft-boned milkfish retort on the water content of soft-boned milkfish.